Quantitative Computed Tomography Measures of Emphysema and Airway Wall Thickness Are Related to Respiratory Symptoms - Grydeland, Thomas B; Dirksen, Asger; Coxson, Harvey O; Eagan, Tomas M. L; Thorsen, Einar; Pillai, Sreekumar G; Sharma, Sanjay; Eide, Geir Egil; Gulsvik, Amund; Bakke, Per S (American journal of respiratory and critical care medicine, 2010)
There is limited knowledge about the relationship between respiratory symptoms and quantitative high-resolution computed tomography measures of emphysema and airway wall thickness. To describe the ability of these measures of emphysema and airway wall thickness to predict respiratory symptoms in subjects with and without chronic obstructive pulmonary disease (COPD). We included 463 subjects with chronic obstructive pulmonary disease (COPD) (65% men) and 488 subjects without COPD (53% men). All subjects were current or ex-smokers older than 40 years. They underwent spirometry and high-resolution computed tomography examination, and completed an American Thoracic Society questionnaire on respiratory symptoms. Median (25th percentile, 75th percentile) percent low-attenuation areas less than -950 Hounsfield units (%LAA) was 7.0 (2.2, 17.8) in subjects with COPD and 0.5 (0.2, 1.3) in subjects without COPD. Mean (SD) standardized airway wall thickness (AWT) at an internal perimeter of 10 mm (AWT-Pi10) was 4.94 (0.33) mm in subjects with COPD and 4.77 (0.29) in subjects without COPD. Both %LAA and AWT-Pi10 were independently and significantly related to the level of dyspnea among subjects with COPD, even after adjustments for percent predicted FEV(1). AWT-Pi10 was significantly related to cough and wheezing in subjects with COPD, and to wheezing in subjects without COPD. Odds ratios (95% confidence intervals) for increased dyspnea in subjects with COPD and in subjects without COPD were 1.9 (1.5-2.3) and 1.9 (0.6-6.6) per 10% increase in %LAA, and 1.07 (1.01-1.14) and 1.11 (0.99-1.24) per 0.1-mm increase in AWT-Pi10, respectively. Quantitative computed tomography assessment of the lung parenchyma and airways may be used to explain the presence of respiratory symptoms beyond the information offered by spirometry.